(untitled) (Journal of Geography and Environmental Management, 2017)
The article considers the features of the temporal distribution of air temperature and atmospheric precipitation in the city of Almaty for 1915-2014. The study of long-term variations in temperature and precipitation, is currently one of the global topical problems. Despite the fact that this issue has been considered for several decades, it is still in a state of debate. In many studies, global climate change is viewed as a consequence of human activities. Also, the work considers the time course of air and precipitation temperature, positive and negative anomalies and extreme values. Mean monthly values of temperature and precipitation are compared for decades. The mean square deviations of the air temperature are calculated and large anomalies (1.5 σ) are determined. For all the seasons in question, years have been found with a deficit of rainfall and abundant rainfall. It is determined that in recent decades the number of positive temperature anomalies has increased.